Investigating the potential immunomodulatory effects of commercial oral probiotic supplements on equine gastrointestinal tract barrier function - Żak-Bochenek, Agnieszka; Żebrowska-Różańska, Paulina; Bajzert, Joanna; Łaczmański, Łukasz; Szponar, Bogumiła; Siwińska, Natalia; Gładysz, Klaudia; Sikorska, Katarzyna; Chełmońska-Soyta, Anna (Frontiers in Immunology, 2025)
BackgroundOral probiotic dietary supplements are widely used in veterinary medicine, including in horses. It is hypothesized that the presence of probiotic strains can both modulate the intestinal microbiota and affect mucosal immunity parameters. Such a study has not yet been conducted in horses.MethodsThis study involved 12 healthy horses, which were randomly divided into a control group and a group that received a commercial oral probiotic formula containing Lactobacillus rhamnosus, Pedioccus acidilactici or Enterococcus faecium for 84 days. Fecal samples were collected from all horses on day 0 (D0), 28 days after starting the probiotic (D28), 56 days (D56), 84 days (D84) and 28 days after stopping the probiotic (DX) treatment. The samples were subjected to microbiome analysis via next-generation sequencing of hypervariable regions V3-V4 and V7-V9 of the 16S rRNA gene for analysis of short-chain fatty acids via HPLC analysis and fecal secretory immunoglobulin A (SIgA) quantification via ELISA.ResultsMicrobiome analysis revealed no significant differences in either alpha or beta diversity parameters between the groups. No probiotic strains were detected in the samples. Significant changes were detected in three taxa: the family Bacteroidales RF16 group, the genus Erysipelotrichaceae UCG-004, and the genus Fibrobacter during the study in both groups. In all the cases, there was a gradual decrease in relative abundance over time. The concentrations of SCFAs, specifically acetic and propionic acids, significantly increased over time in both groups according to the generalized linear mixed effects (GLME) model. There were no significant differences in fecal SIgA secretion.ConclusionThe present study revealed no effect of the use of a commercial probiotic dietary supplement on either mucosal immunity or the composition of the intestinal microbiota.